Peran Badan Permusyawaratan Desa Dalam Meningkatkan Efetivitas Pemerintahan di Desa Koreng Kecamatan Tareran Kabupaten Minahasa Selatan - Kawung, Noffy (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract: The conception of the village as Consultative Bodies that are desired by Act No. 22 of 1999 is to provide powerful control functions to the village chief in addition, Consultative bodies of the village is known for the introduction of the legislative Institutions, and have the authority the authority legislation generally in the village. The quality of human resources (public), including the village government apparatus and Leadership as well as members of the Village institutions in the improvement of the effectiveness of implementation of giliranya inhibits the Government village, so there is also an impact on the effectiveness of Implementation the Government accelerated the slow pace of the village itself. Konstalasi that causes BPD do not proactively with his duties because of the factor of human resources (HR) members. Based on explanation above, the authors are encouraged to conduct research on the system of Government with the title role of the Consultative bodies of the village of Efetivitas in improving governance at the village of Tareran Sub-district Koreng South Minahasa Regency. This research uses qualitative research methods deskriptis with the data analysis techniques, described in the form of description sentences by giving interpretation/interpretation based on direct interviews conducted with a sample of existing research object or the respondent is there, so it can be used by way of presentation techniques The research results and conclusions stated that perluanya there is a good relationship between BPD and the Government of the village, an increase in the Metal of the BPD was also in a sense quite necessary, in order that they may be liable with all their duties and responsibilities. Referring to the conclusions above, in order that the Government shall recommend to hold special training to BPD so that in carrying out tasks they can optimally, it needs also the existence of a relationship between the Government of the village and a tub of BPD as a partner.